The Influence of Ovarian Stromal/Theca Cells During In Vitro Culture on Steroidogenesis, Proliferation and Apoptosis of Granulosa Cells Derived from the Goat Ovary. Issue 1 (21st November 2013) - Qiu, M; Liu, J; Han, C; Wu, B; Yang, Z; Su, F; Quan, F; Zhang, Y
Contents Early follicular development is closely related to oocyte‐granulosa cells‐ovarian stromal cells/theca cells. The aim of the present study was to investigate the effects of ovarian cortical, medullary stromal and theca cells on oestradiol and progesterone biosynthesis, proliferation and apoptosis of goat ovary granulosa cells in vitro. Using Transwell coculture system, we evaluated steroidogenesis, cell proliferation and apoptosis, and some molecular expressions regarding steroidogenic enzyme, luteinizing hormone receptor and apoptosis‐related genes in granulosa cells. The results indicated that ovarian stromal/theca cells were able to stimulate oestradiol and progesterone production, promote cell proliferation and inhibit apoptosis of granulosa cells. Among all the three kinds of cells, theca cells affected strongly on granulosa cell function, and ovarian medullary stromal cells had the weakest effect on granulosa cells. These findings would provide an important knowledge of cell interaction among follicular cells during follicular development.